2008
DOI: 10.1109/mra.2008.929927
|View full text |Cite
|
Sign up to set email alerts
|

Mobile robotic teleguide based on video images

Abstract: obot teleoperation is inherently related to sensor data transmission. Sensor data can be interpreted by the robotic system before being transmitted and presented to a user. This typically happens with sonar and laser sensors. In other cases, sensor data can directly be presented to a user to let him or her interpret the transmitted information. This happens, for example, with visual data. Robot teleoperation systems typically rely on two-dimensional (2-D) displays. These systems suffer from many limitations, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
0
17
1
Order By: Relevance
“…Compared to previous studies that found advantages of stereo display when navigating with video-based or egocentric 3D user interfaces (Lee & Kim, 2008;Livatino et al, 2008;Chen et al, 2014;Livatino et al, 2010), the additional environment data available through the point cloud display and global 3D environment mapping in the user interface may explain why the present study did not find significant differences between display conditions.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Compared to previous studies that found advantages of stereo display when navigating with video-based or egocentric 3D user interfaces (Lee & Kim, 2008;Livatino et al, 2008;Chen et al, 2014;Livatino et al, 2010), the additional environment data available through the point cloud display and global 3D environment mapping in the user interface may explain why the present study did not find significant differences between display conditions.…”
Section: Resultscontrasting
confidence: 91%
“…Studies have suggested that stereoscopic display improves users' task performance and environment judgments in such domains as reaching for objects, positioning and resizing objects, and path tracing in virtual environments (Arsenault & Ware, 2004;Hubona et al, 2004;Sollenberger & Milgram, 1993;Ware & Franck, 1996;Barfield et al, 1999), or in video-based robotic telemanipulation (Edmondson et al, 2012;Drascic, 1991;Hutto et al, 2004), video-based remote robot navigation (Lee & Kim, 2008;Livatino et al, 2008;Chen et al, 2014), and remote robot navigation based on egocentric 3D visualizations extrapolated from 2D laser scanner data (Livatino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binocular disparity, not available when using standard displays and realized through stereoscopic technology, can be a powerful cue to depth. Compared to monoscopic display, stereoscopic display has shown to improve users' task performance and accuracy of environment judgments in a number of domains related to the present user interface like reaching for objects [53], positioning and resizing objects [54], and path tracing [55][56][57] in virtual environments, video-based robotic telemanipulation [50,58,59], video-based remote robot navigation [49,60,61], and remote robot navigation based on egocentric 3D visualizations extrapolated from 2D laser scanner data [62].…”
Section: Investigating Stereoscopic Displaymentioning
confidence: 99%
“…Livatino et al (2008) performed an evaluation comparing monoscopic and stereoscopic viewing in performance of a UGV navigation task. The task involved navigation of a UGV over a short distance (3.5m) through a field of obstacles.…”
Section: Perception For Teleoperationmentioning
confidence: 99%